Characteristics of size-resolved atmospheric inorganic and carbonaceous aerosols in urban Shanghai. (October 2017) - Ding, X.X.; Kong, L.D.; Du, C.T.; Zhanzakova, A.; Fu, H.B.; Tang, X.F.; Wang, L.; Yang, X.; Chen, J.M.; Cheng, T.T.
Abstract: Size-segregated aerosol particles were collected with a 10-stage Micro-Orifice Uniform Deposit Impactor (MOUDI) at an urban site in Shanghai, China for four non-consecutive months representing four seasons from 2015 to 2016. Chemical composition, including water-soluble ions as well as organic carbon (OC), elemental carbon (EC) and secondary organic carbon (SOC) of size-resolved (0.056–18 μm) atmospheric aerosols in four seasons and in different polluted cases were studied. The size distributions of sulfate, nitrate and ammonium (SNA) and carbonaceous aerosol (OC, EC and SOC) were discussed and the potential sources of PM1.8 -associated secondary species (SO4 2−, NO3 −, SNA and SOC) in different seasons were identified by potential source contribution function (PSCF) model. Results showed that atmospheric ultrafine and fine particle pollution in Shanghai were very serious during the study period. Most of the water-soluble ions tended to be enriched in fine particles, especially being abundant in the droplet mode in polluted cases. Compared with sulfate, size distributions of nitrate and ammonium presented more significant seasonal variations and showed distinctive characteristics in polluted days. Abundant nitrate was concentrated in fine particles in cold seasons (spring and winter), whereas it was enriched in coarse mode during summer and autumn. The droplet mode sulfate with high concentration did not result in the aggravation of air pollution, while the nucleation mode sulfate may have made a great contribution to the air pollution in urban Shanghai. It was also found that the formation of air pollution in urban Shanghai had a significant link with nitrate and ammonium, especially with nitrate and ammonium in condensation mode and droplet mode, and the contribution of sulfate to the pollution formation in Shanghai would somehow be surpassed by the increasing nitrate and ammonium. OC and EC concentrations from spring to winter were found to be 11.10, 7.10, 12.30, 20.16, and 3.73, 2.84, 4.63, 7.10 μg m −3, respectively, distinctly presenting the summer minima and winter maxima in this study. The maximum OC/EC was in the droplet mode and the minimum was in the nucleation mode for both clean and polluted days. The great contribution of SOC to OC in droplet mode and the occurrence of PM pollution necessarily had an important bearing on the SOC formation in droplet mode particles. Particle acidity may play a key role in secondary organic aerosol formation and the particles with the size of 0.056–0.1 μm was the most sensitive particles to acid catalysis in SOA formation. The similar PSCF results of PM1.8 -associated SOC to those of SO4 2−, NO3 − and SNA indicated possible connections between the formation of SOC and secondary inorganic species in PM. Graphical abstract: Highlights: Atmospheric ultrafine and fine particle pollution in Shanghai were very serious. Air pollution had close links with NO3 − and NH4 + in condensation and droplet mode. Great contribution of SOC in droplet mode to OC and PM pollution. Possible connections between the formation of SOC and SNA were revealed by PSCF.